2021
DOI: 10.4236/gep.2021.910003
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as a Soil Ameliorant: How Biochar Properties Benefit Soil Fertility—A Review

Abstract: In recent years, biochar has received great attention among researchers worldwide. This carbon-rich material, mainly produced from residues from agriculture and forestry, holds a wide range of properties, e.g. large specific surface area, high cation exchange capacity, and substantial nutrient contents, that can have beneficial effects when added to soils. This review is giving a brief introduction to biochar properties and how feedstock, pyrolysis temperature, and time influence these properties. As the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 145 publications
5
7
0
3
Order By: Relevance
“…Our study showed that the soil fertility index (SFI) does not seem to be affected by increased doses of mineral fertilizers, although they may be associated with environmental risks such as water pollution ( [25] [27] [28]). However, many research results shown that bio-fertilizers, due to their richness in organic matter and exchangeable bases [29], are very beneficial in improving the soil fertility index as suggested by our results. This suggests that there is a real opportunity to valorize these alternative sources of organic matter (bio-waste or Biochar) [29] and subsequently sequester carbon in order to contribute to GHG reduction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our study showed that the soil fertility index (SFI) does not seem to be affected by increased doses of mineral fertilizers, although they may be associated with environmental risks such as water pollution ( [25] [27] [28]). However, many research results shown that bio-fertilizers, due to their richness in organic matter and exchangeable bases [29], are very beneficial in improving the soil fertility index as suggested by our results. This suggests that there is a real opportunity to valorize these alternative sources of organic matter (bio-waste or Biochar) [29] and subsequently sequester carbon in order to contribute to GHG reduction.…”
Section: Discussionsupporting
confidence: 59%
“…However, many research results shown that bio-fertilizers, due to their richness in organic matter and exchangeable bases [29], are very beneficial in improving the soil fertility index as suggested by our results. This suggests that there is a real opportunity to valorize these alternative sources of organic matter (bio-waste or Biochar) [29] and subsequently sequester carbon in order to contribute to GHG reduction. However, the challenge of the sanitary side effect of bio-waste must be mastered upstream, through advisory support, to preserve the quality of food and the health of farmers (handling) and consumers.…”
Section: Discussionsupporting
confidence: 59%
“…In the recent decade, scientists have viewed biochar as a modifier and guarantee of soil sustainability due to its adsorption properties (Kamali et al, 2022). The improvement of plant productivity through biochar use is due to its porous structure and ability to retain water (Asadi et al, 2021; Beusch, 2021), nutrients (Ghorbani et al, 2019), and limit the absorption of pollutants such as heavy metals by plant roots (Amirahmadi et al, 2020). The literature has the deterioration of structural properties of biochar to boost its efficiency and rapid environmental stability (Deng et al, 2020; Ghorbani et al, 2021; He et al, 2019; Li et al, 2017; Mia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in recent years have revealed the positive effects of biochar amendment on physical and chemical soil properties (Beusch 2021), such as the increase of cation exchange capacity (CEC) (Das et al 2021;Liang et al 2006) and soil water-holding capacity (e.g., Abel et al 2013;Bruun et al 2014;Hien et al 2021). Furthermore, an increase in crop yield has been documented for different biochars, soil types, and regions (e.g., Gopal et al 2020;Jeffery et al 2011;Steiner et al 2007;Xu et al 2015;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%